Application of Technology in Improving Primary School Students' Digital Literacy Skills - Nur Wahyuni; Dinda Widyastika; Nabila Nabila (FKIP, Universitas Palangka Raya, 2025)
Literacy is an individual's ability to manage and understand information through reading and writing activities. This skill is closely related to language skills because it includes aspects of speaking, reading, writing, counting and problem-solving skills. In other words, literacy includes language abilities and skills, including reading, writing, speaking, counting, and problem solving at a certain level needed in everyday life. This research uses a literature study approach as the main method of data collection. In the process, the researcher conducted an in-depth study and understanding of various relevant theories from literature sources.Today, in the digital era, digital literacy is a very important ability for elementary school students to have. The development of information and communication technology has changed learning methods, so it is important that students have sufficient ability to access, evaluate and use digital information effectively. Digital literacy of primary school students includes various important elements. First, digital literacy enables students to develop skills in utilizing digital technology, including surfing the internet, understanding hardware and software, and using productivity applications. Second, digital literacy teaches students about the safety and ethical aspects of using technology, such as maintaining online privacy, protecting personal data and avoiding cyberbullying.